Implementation of Project Based Learning in Elementary Schools - Afitri, Afitri (Program Magister Teknologi Pendidikan Universitas Jambi, 2017)
This research aims to describe the implementation of project-based learning in the VA class of State Elementary School 131/IV Jambi City. This research was conducted at State Elementary School 131/IV Jambi City. This research is qualitative research with a phenomenological type of research. The data obtained in the research is in the form of descriptions or narratives regarding the implementation of project-based learning in elementary schools for class VA students. The data source in this research is the VA class teacher with the data collection techniques used are observation, interviews and documentation. The results of this research are in the form of a narrative regarding the implementation of project-based learning in elementary school VA classes. The implementation of project-based learning includes learning planning and learning implementation. The application of project-based learning has an impact on the learning process. Students participate directly in creating projects, finding out the use of the projects they create and displaying and explaining the projects in front of the class. Students look active, confident and enthusiastic. From the results of this research it can be concluded that project based learning in the VA class of State Elementary School 131/IV Jambi City in theme 6 subtheme 1 learning 2 science content, in Mathematics Chapter 1 content and theme 6 subtheme 2 learning 2 has been implemented. Project-based learning creates enthusiasm, enthusiasm, confidence and activeness in students during learning.